1965
DOI: 10.1111/apm.1965.63.4.533
|View full text |Cite
|
Sign up to set email alerts
|

Premitotic Uptake of Tritiated Thymidine by Mast Cells

Abstract: Hccc ivc d 8 . x . 6~Mast ce ll s play an important ro le in th e physiology of co nnec tive li ssues. Th eir ca pability of synth es is and r elease of ground sub s tan ce compo n ents which ma y hind ti ssu e walc r places th ese cell s in a lwy p osi tion in lh e m ec hani sm of g row th , r egen e ration, and r epa ir as well a s in severa l palhological processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1969
1969
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Whilst performing cytophotometric DNA measurements, we encountered some tetraploid MC in lymph nodes (Queisser et al 1967). After application of 'H-thymidine, MC show an extremely low labelling index; the maximum index appears after a time lapse of 3-5 days (Asboe-Hansen et al 1965). This indicates that MC precursors take up the label while not identifiable as MC.…”
Section: Origin Of Mast Cellsmentioning
confidence: 99%
“…Whilst performing cytophotometric DNA measurements, we encountered some tetraploid MC in lymph nodes (Queisser et al 1967). After application of 'H-thymidine, MC show an extremely low labelling index; the maximum index appears after a time lapse of 3-5 days (Asboe-Hansen et al 1965). This indicates that MC precursors take up the label while not identifiable as MC.…”
Section: Origin Of Mast Cellsmentioning
confidence: 99%
“…Alternatively, tnitotic division, proliferation from precursor cells and/or transformation from already differentiated cells may be involved. In contrastto the mature mast celis,which are generally considered to be mitotically inactive, the immature mast cells may comprise a mitotic pool (Asboe-Hansen et al 1965, Combs, Lagunoff and Benditt 1965, Miller and Coole 1968. Mast cells most likely arise from undifferentiated mesenchymal cells in the loose connective tissue (Combs et al 1965, Sagher andEven-Paz 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Campbell et al (1967), working with 59Fe, cell smears and liquid emulsion techniques, have also reported a good fit with Poisson theory, modified to take into account variations in cell diameter. Similarly Asboe-Hansen et al (1965) have reported a Poisson distribution from background counts, and a distribution of counts over labelled cells which can be accounted for by a Poisson distribution plus a contribution due to the variance of cell area.…”
Section: Introductionmentioning
confidence: 91%